SILENT STROKE, LOUD SYMPTOMS : ISOLATED APHASIA IN HYPERTENSIVE EMERGENCY-INDUCED TRANSIENT ISCHEMIC ATTACK - Nona Suci Rahayu; Putri Irmayani; Ari Bandana Tasrif (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2024)
Aphasia is a neurological dysfunction that arises due to disturbances in the brain regions responsible for language processing. These areas are predominantly localized within the frontal cortex and the temporoparietal regions, which regulate both motor and sensory speech functions. Disruptions in these areas may result from ischemic conditions affecting the brain. Isolated cases of aphasia without other accompanying neurological deficits are rarely reported. This article presents a case study of a 66-year-old female patient with a history of chronic hypertension who presented to the emergency unit with a sudden onset of speech difficulties without any other neurological impairments. Initial examination revealed significantly elevated blood pressure at 220/110 mmHg, accompanied by severe headache. A diagnosis of Transient Ischemic Attack (TIA) was supported by clinical findings that resolved within 24 hours and imaging from a non-contrast head CT scan, which showed normal brain parenchyma. The primary focus of initial management was the restoration of cerebral blood flow through the administration of neuroprotective agents and antiplatelet therapy, aiming to optimize cerebral perfusion and achieve clinical recovery of aphasia. This case analysis highlights the importance of prompt and appropriate management in hypertensive emergencies, emphasizing the detection of clinical signs of TIA or complete stroke, even in localized neurological deficits without additional accompanying symptoms.